Hubungan Kepatuhan Minum Obat dengan Kekambuhan Pasien Skizofrenia di Wilayah Kerja Puskesmas Kasihan II Bantul Yogyakarta - Putri Lia Sari; Mulyanti, Mulyanti; Kurniawan, Catur; Dewi, Ika Mustika (LPPM Hang Tuah Pekanbaru, 2024)
Schizophrenia is a severe mental disorder that necessitates long-term care and treatment. One of the frequent problems encountered in the treatment and medication of schizophrenia patients is drug withdrawal (20%). Drug withdrawal occurs when patients fail to comply with their medication regimen, and it is recognized as a significant factor that causes relapse. People with schizophrenia who experience a relapse in the region are (10%). Objective of the research Investigate the relationship between medication adherence and relapse in the working area of Kasihan II Community Health Center, Bantul, Yogyakarta. This research is correlational research carried out by utilizing a quantitative method. A cross-sectional approach was employed as the research design. The research was conducted within the working area of Kasihan II Community Health Center in Bantul, Yogyakarta, encompassing a population of 238 respondents and a sample size of 78 respondents. The research employed purposive sampling as the sampling technique. Data collection was carried out through door-to-door interviews. A recurrence measurement questionnaire and a Medication Adherence Rating Scale (MARS-10). The data obtained were then analyzed using the Kendal Tau test. The research found that 50 respondents (64.1%) had a high level of medication adherence, while 50 respondents (64.1%) had a low level of relapse. Therefore, it is hoped that the provision of knowledge about drugs such as the effects, benefits, and functions of drugs to ODS will be given attention so that they can understand and understand the drugs they are taking.